2017
DOI: 10.1371/journal.pgen.1006974
|View full text |Cite|
|
Sign up to set email alerts
|

mlh3 mutations in baker’s yeast alter meiotic recombination outcomes by increasing noncrossover events genome-wide

Abstract: Mlh1-Mlh3 is an endonuclease hypothesized to act in meiosis to resolve double Holliday junctions into crossovers. It also plays a minor role in eukaryotic DNA mismatch repair (MMR). To understand how Mlh1-Mlh3 functions in both meiosis and MMR, we analyzed in baker’s yeast 60 new mlh3 alleles. Five alleles specifically disrupted MMR, whereas one (mlh3-32) specifically disrupted meiotic crossing over. Mlh1-mlh3 representatives for each class were purified and characterized. Both Mlh1-mlh3-32 (MMR+, crossover-) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 97 publications
(230 reference statements)
6
44
0
Order By: Relevance
“…However, in pch2∆ mlh3∆ double mutants, COs were reduced 20-35% relative to pch2∆ MLH3 ( Figure 3B; average pch2∆ mlh3∆/pch2∆ = 74 ± 7%), as was previously observed for inserts at URA3 and HIS4 (MEDHI et al 2016). A quantitatively similar MutLg-dependence has also been observed for Spo11-initiated COs in pch2∆ mutants, both genome-wide (pch2∆ mlh3∆ / pch2∆ = 73% (CHAKRABORTY et al 2017) and for individual genetic intervals (pch2∆ / pch2∆ mlh3∆ = 75%, calculated from combined data of NISHANT et al 2008;ZANDERS AND ALANI 2009;AL-SWEEL et al 2017;CHAKRABORTY et al 2017). Thus, the absence of Pch2 increases the MutLg-dependence of VDEinitiated COs at many loci, while decreasing the MutLg-dependence of VDE-initiated COs at HIS4 and of Spo11-initiated COs.…”
Section: Increased Mlh3-dependence Of Vde-initiated Cos In Pch2∆ Mutantssupporting
confidence: 83%
See 2 more Smart Citations
“…However, in pch2∆ mlh3∆ double mutants, COs were reduced 20-35% relative to pch2∆ MLH3 ( Figure 3B; average pch2∆ mlh3∆/pch2∆ = 74 ± 7%), as was previously observed for inserts at URA3 and HIS4 (MEDHI et al 2016). A quantitatively similar MutLg-dependence has also been observed for Spo11-initiated COs in pch2∆ mutants, both genome-wide (pch2∆ mlh3∆ / pch2∆ = 73% (CHAKRABORTY et al 2017) and for individual genetic intervals (pch2∆ / pch2∆ mlh3∆ = 75%, calculated from combined data of NISHANT et al 2008;ZANDERS AND ALANI 2009;AL-SWEEL et al 2017;CHAKRABORTY et al 2017). Thus, the absence of Pch2 increases the MutLg-dependence of VDEinitiated COs at many loci, while decreasing the MutLg-dependence of VDE-initiated COs at HIS4 and of Spo11-initiated COs.…”
Section: Increased Mlh3-dependence Of Vde-initiated Cos In Pch2∆ Mutantssupporting
confidence: 83%
“…In contrast to what was seen for VRS inserts at HIS4, where COs were reduced dramatically in mlh3∆ mutants (to ~40% of wild-type levels), COs in the same sequences inserted at all other loci were only modestly affected, with COs in mlh3∆ ranging from ~80% to ~115% of wild type (mean = 91 ± 12%; Figure 2D); NCOs were similarly unaffected ( Figure 2E, F). These results indicate that, in contrast to Spo11-initiated COs, which are reduced about 2-fold in mlh3∆ mutants (WANG et al 1999;KHAZANEHDARI AND BORTS 2000;KIRKPATRICK et al 2000;TSUBOUCHI AND OGAWA 2000;HOFFMANN et al 2003;ARGUESO et al 2004;NISHANT et al 2008;AL-SWEEL et al 2017;CHAKRABORTY et al 2017), most COs at the VDE break sites are formed independent of MutLg, irrespective of the chromosome size, distance from centromere or telomere, or Hop1-enrichment in their vicinity. Thus, at most insert loci in otherwise wild-type cells, VDE-initiated recombination differs from Spo11-initiated recombination and more closely resembles mitotic recombination, in that NCOs are in excess over COs (ESPOSITO 1978;LICHTEN AND HABER 1989;IRA et al 2003;DAYANI et al 2011) and, with the exception of those formed in inserts at HIS4, VDE-initiated COs are largely MutLg-independent.…”
Section: Vde-initiated Cos Are Mlh3-independent At Most Insert Sitesmentioning
confidence: 88%
See 1 more Smart Citation
“…Molecular incompatibilities between certain alleles of the CO formation or CO interference machinery may account for these cross-specific differences. To investigate this hypothesis further, we analysed the frequency and distribution of COs within a mlh3 Δ S288c x YJM789 background containing a functional copy of the SK1 MLH3 allele ( SK1-MLH3 ) 45 . Surprisingly, introduction of the SK1 MLH3 allele is sufficient to reduce the global strength of CO interference and produce a CO distribution identical to that of S288c x SK1 wild type (p = 0.91; Two-sample KS Test) (Supplementary Fig.…”
Section: Supplementary Discussionmentioning
confidence: 99%
“…In budding yeast, the endonuclease Mlh1-Mlh3 interacts with Sc Msh4-Msh5 to resolve dHJs, although how the asymmetry in resolution occurs is not understood, particularly because the junctions form hundreds of bps apart from each other. One proposed model for MutSg function is the stabilization of dHJs to prevent dissolution before resolution by MutLg (20,31,73). Fishel and co-workers have proposed that multiple MutSg complexes form sliding clamps around the junction site, potentially facilitating asymmetric resolution of the junctions (31), whereas others have suggested that the polymerization of Mlh1-Mlh3 enables asymmetric junction resolution (27).…”
Section: Discussionmentioning
confidence: 99%